From Struggle to Achievement: An Entrepreneurial Journey of Tara Bahadur Kunwar - Adhikari, Rajendra P. (AMC Indian Journal of Entrepreneurship, 2019)
Entrepreneurship is taught in class rooms, and universities are putting in effort into producing entrepreneurs these days. Entrepreneur is most commonly interpreted as an individual who "does not work as an employee" and takes risks for future benefits. This article presents the story of an individual, whose journey towards the unknown future transformed him into a known personality of the present time in Nepal. He is successfully running his business. Hence, the purpose of this article is to present the struggle and achievements of Tara Bahadur Kunwar as an entrepreneur to inspire many potential entrepreneurs to become successful. Moreover, struggle and achievement of Tara Bahadur will serve as an example of how an individual can transform his/her fate with perseverance and hard work. Tara Bahadur is the person who had to leave his birth place while he was studying in grade two and took a journey to the capital city of Nepal, Kathmandu in the pursuit of his future. The unknown future, was this for better study or for better work? This article presents a picture of the society where persons like Tara Bahadur used to live. As a case, this article is expected to serve as a record of a society that existed in 1960s, the extent of an individual's struggle for survival, and the story of a person who was able to transform his life and has become a successful entrepreneur.